Respiratory Syncytial Virus and Other Noninfluenza Respiratory Viruses in Older Adults - Kodama, Fumihiro; Nace, David A; Jump, Robin L P (Infectious disease clinics of North America, 2017)
Respiratory viral infections may cause serious complications for older adults, including residents of long-term care facilities (LTCFs). Although influenza is the most common cause of viral respiratory infections among older adults, several other respiratory viruses also cause significant morbidity and mortality, most notably respiratory syncytial virus. Other noninfluenza respiratory viral pathogens include human metapneumovirus, parainfluenza virus, rhinovirus, coronavirus, and adenovirus. All of these may cause outbreaks among LTCF residents. Recently developed rapid diagnostic molecular tests may clarify the epidemiology of these viruses and have potential, through early identification, to limit the severity of outbreaks among older adults living in LTCFs.